Femmes et genre en Irak - Ali, Zahra; Ghosn, Nada (Éditions Syllepse, 2022)
"Les nombreuses questions sociologiques soulevées par Zahra Ali sur les femmes, le genre et le féminisme en Irak ont trouvé des réponses à travers son expérience quotidienne dans le pays, de 2010 à 2019, ce dont elle rend compte avec virtuosité et profondeur dans son livre. Virtuosité, car pour une journée de travail de terrain à Bagdad, il lui fallait passer une douzaine de checkpoints pour aller de la maison familiale au centre-ville. Profondeur, car ses observations ethnographiques nous permettent de comprendre comment un des pays les plus avancés de la région en termes d'éducation, de santé, d'emploi et de droits juridiques des femmes a pu devenir ce territoire militarisé contrôlé par des hommes armés, fragmenté, si difficilement vivable pour ses habitants, et encore plus pour les femmes. Son étude, mêlant ethnographie et histoire sociale, politique et orale, nous offre une compréhension des expériences sociales, économiques, politiques et féministes des femmes irakiennes. Le regard de Zahra Ali postule que les femmes, les questions de genre et les luttes féministes en Irak doivent être analysées au moyen d'un prisme complexe, relationnel et historique, sans avoir recours à l'argument d'une « culture » ou d'un « islam » indifférenciés afin d'expliquer des réalités sociales, économiques et politiques. Cet ouvrage traite autant des femmes, du genre et du féminisme en Irak qu'il est un ouvrage féministe sur l'Irak. Il contribue aux débats féministes et propose une analyse féministe postcoloniale et transnationale de l'histoire socio-politique contemporaine de l'Irak."-- Quatrième de couverture.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme décolonial; féminisme islamique; histoire et politique; irak; premier cycle; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit